A DFT Study on the Mechanism of the Annulation Reaction of Trichloronitroethylene with Aniline in the Synthesis of Quinoxalinone-N-oxides - ERDEM, SAFİYE (AMER CHEMICAL SOC, 2009)
The new annulation reaction of trichloronitroethylene with aniline results in the formation of a quinoxalinone-N-oxide derivative. The mechanism of this one-pot annulation reaction between trichloronitroethylene (TCNiE) and anilines has been extensively investigated with B3LYP/6-31+G** methodology. Five different paths (1-5) were proposed and modeled by using this method. These paths were compared in terms of the activation energies of their rate-determining steps and in regard to the experimental findings. Paths 3 and 5, proceeding via four-membered heterocyclic rings, were found to be the most plausible paths with activation energies of 32 and 29 kcal/mol for the rate-determining steps, respectively. The effects of substituent, solvent, temperature, and computational method on these steps were also investigated. The results showed that path 5 is the most plausible mechanism for the annulation reaction of trichloronitroethylene with aniline.
Keywords: DENSITY-FUNCTIONAL THERMOCHEMISTRY; TRANSITION-STATE GEOMETRIES; POLYHALOGENATED NITROBUTADIENES; ADJUSTABLE-PARAMETERS; ACTIVATION-ENERGIES; BIOLOGICAL-ACTIVITY; BARRIER HEIGHTS; EXACT-EXCHANGE; DERIVATIVES; CHEMISTRY